Guia para a prática do enfermeiro da atenção primária em avaliação e tratamento da pessoa com úlcera venosa - Colombi, Amanda Ferreira de Almeida (2022)
Ulcers of vascular etiology are among the most prevalent lesions in studies carried out in the country. Venous ulcers are difficult to heal, have a high recurrence rate and interfere with the quality of life of people who are affected. Thus, the treatment of these injuries is part of the routine of nurses in primary health care. Considering the need to guide nurses' care for patients with venous ulcers, it is essential to establish protocols that contribute to changing the practice of health care. These provide a guided and grounded practice, directing professionals towards an instrumented and quality care. Objectives: To identify nurses' self-knowledge in the treatment and assessment of people with venous ulcers in the lower limbs. Check documents in the area of nursing in the assessment and treatment of people with venous ulcers in the lower limbs. To structure the clinical guide on the assessment and treatment of people with venous ulcers in the lower limbs for the practice of nurses in primary health care. To develop a clinical guide on the assessment and treatment of people with venous ulcers in the lower limbs for the practice of nurses in primary health care. Methodology: This is a methodological study that took place in 2 stages for the construction of the clinical guide: 1) situational diagnosis 2) elaboration of the clinical guide. Results: 40 nurses participated in the study, of which 34 (85%) were female. The majority, 87.5%, answered that they had attended a lato sensu postgraduate course and of these 2 attended the area of wound care, and 10% answered that they had attended a stricto sensu postgraduate course. The most used products for treatment mentioned were Essential Fatty Acids (32.5%) and Unna boot (15%). The highest frequency (20%) of the answer “none” was in the 3G question, which addressed knowledge about the application of elastic compression therapy. The clinical guide will be built according to the responses of the self-assessment instrument regarding the weaknesses reported in the responses to support the care process of nurses undergoing treatment and assessment of venous ulcers. Product: Clinical guide for assistance to people with venous ulcers in primary health care. Conclusion: It is believed that this guide will be an object of conduction of the nurse's praxis in the evaluation and treatment of the person with VU in the city of Vila Velha with quality and assertiveness. It can positively impact the lives of people affected by UV.